THE ROLE OF INNOVATIVE TECHNIQUES IN TEACHING ENGLISH - Rustamova Adash Eshankulovna; Axtamova Durdona Alisherovna (Scholar Express Journals, 2024)
“There is nothing permanent except change,” says Heraclites, the pre Aristotelian Greek philosopher. Change is the law of nature. In the developing world, it is difficult to imagine our day without updated- techniques. It becomes as a daily needs day by day. In every field of today’s modern society. Especially, in the educational purpose is used widely. With the help of newer methods and techniques, a lot of conveniences are being created for students
Keywords: technique; cellular phones; activity; illustration